Bioconcentration and Acute Intoxication of Brazilian Freshwater Fishes by the Methyl Parathion Organophosphate Pesticide. (3rd August 2015) - Bosco de Salles, João; Matos Lopes, Renato; de Salles, Cristiane M. C.; Cassano, Vicente P. F.; de Oliveira, Manildo Marcião; Cunha Bastos, Vera L. F.; Bastos, Jayme Cunha
Abstract : Three species of freshwater Brazilian fishes (pacu, Piaractus mesopotamicus ; piavussu, Leporinus macrocephalus, and curimbatá, Prochilodus lineatus ) were exposed to an acute dose of 5 ppm methyl parathion organophosphate pesticide. Three to five individuals per species were exposed, one at a time, to 40 liters tap water spiked with Folidol 600. Pesticide concentrations and cholinesterase (ChE) activities were evaluated in serum, liver, brain, heart, and muscle. The bioconcentration of methyl parathion was similar for all studied fishes. Brain tissue showed the highest pesticide concentration, reaching 80 ppm after exposure for 30 min to methyl parathion. Three to 5 hours of 5 ppm methyl parathion exposure provoked the death of all P. lineatus at 92% brain AChE inhibition, whereas fish from the other two species survived for up to 78 hours with less than 80% brain AChE inhibition. Our results indicate that acute toxic effects of methyl parathion to fish are correlated with brain AChE sensitivity to methyl paraoxon.